2004
DOI: 10.1590/s0100-69912004000500002
|View full text |Cite
|
Sign up to set email alerts
|

Recorrência em pacientes portadores de melanoma cutâneo submetidos a biópsia de linfonodo sentinela: seguimento mediano de 37 meses

Abstract: OBJETIVO: A biópsia de linfonodo sentinela (BLS) representa um avanço na cirurgia oncológica para o microestadiamento do melanoma. Apresentamos nossa experiência dando ênfase para a recorrência. MÉTODO: A BLS foi realizada em 133 pacientes portadores de melanoma cutâneo localizado envolvendo linfocintilografia, mapeamento linfático e detecção gama intra-operatórios em todos os pacientes. O exame histopatológico foi realizado por HE e imunohistoquímica (IHC). RESULTADOS: Encontrou-se LS em 128 pacientes (96,2%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In skin melanomas, the malignant changes in melanocytes start at the membrane level, which undergo degradation of basal membrane and subsequent invasion of dermis. The morphological characteristic of the dermis remains morphochemically unchanged, 51 which could explain this higher protein level. We found that six MEL spectra were misclassified as BCC.…”
Section: Discussionmentioning
confidence: 97%
“…In skin melanomas, the malignant changes in melanocytes start at the membrane level, which undergo degradation of basal membrane and subsequent invasion of dermis. The morphological characteristic of the dermis remains morphochemically unchanged, 51 which could explain this higher protein level. We found that six MEL spectra were misclassified as BCC.…”
Section: Discussionmentioning
confidence: 97%